Kepemimpinan Situasional Kepala Sekolah dalam Membangun Sumber Daya Manusia Pada Pendidikan - Siti Nur Afifah; Istikhori Istikhori; Rima Rima; Nazrul Jimatul Rizki; Rubi Babullah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Situational leadership is a leadership approach that emphasizes the leader's flexibility and adaptability in adapting the leadership style to the situation and needs of subordinates. This research aims to explore the application of situational leadership in managing human resources in the field of education through a literature review method. Through a comprehensive literature analysis, it was found that situational leadership is effective in improving the performance and motivation of teaching staff and educational staff. Situational leadership allows educational leaders to adopt the most appropriate style, ranging from directive to supportive, according to the level of preparedness and competence of subordinates. In addition, this research also highlights that situational leadership can help in overcoming various challenges in a dynamic educational environment, including curriculum changes, professional development needs, and improving the quality of learning. The analyzed literature shows that the application of situational leadership contributes significantly to achieving broader educational goals and improving the quality of human resources in educational institutions. These findings emphasize the importance of situational leadership training and development for educational leaders to achieve optimal results.